-5-3(4y-2)=-1-9y

Simple and best practice solution for -5-3(4y-2)=-1-9y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-3(4y-2)=-1-9y equation:


Simplifying
-5 + -3(4y + -2) = -1 + -9y

Reorder the terms:
-5 + -3(-2 + 4y) = -1 + -9y
-5 + (-2 * -3 + 4y * -3) = -1 + -9y
-5 + (6 + -12y) = -1 + -9y

Combine like terms: -5 + 6 = 1
1 + -12y = -1 + -9y

Solving
1 + -12y = -1 + -9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9y' to each side of the equation.
1 + -12y + 9y = -1 + -9y + 9y

Combine like terms: -12y + 9y = -3y
1 + -3y = -1 + -9y + 9y

Combine like terms: -9y + 9y = 0
1 + -3y = -1 + 0
1 + -3y = -1

Add '-1' to each side of the equation.
1 + -1 + -3y = -1 + -1

Combine like terms: 1 + -1 = 0
0 + -3y = -1 + -1
-3y = -1 + -1

Combine like terms: -1 + -1 = -2
-3y = -2

Divide each side by '-3'.
y = 0.6666666667

Simplifying
y = 0.6666666667

See similar equations:

| 30=-3x-9 | | 2x+120+20=180 | | -3(x-4)+8=2 | | F=1/3n^2m | | x+(3x+3)=43 | | 5-3sin^2x-4cosx=4 | | .25(24+1)=.5(y+2) | | x+20=4x-13 | | 4-5v+5=2v-12 | | 0=3x^2-12x+6 | | 6-v=v+16 | | .25(18+1)=.5(y+2) | | 11y/15×3/5y | | 12+3x-3x= | | 24a-8-100=-2(4-7a) | | -8a-8=27-a | | 3+5y=-7 | | h(4)=1/4x-1 | | R-0.58R=192.44 | | (-2x+4)+3(4x-5)=10x-11 | | -8a-8=2-a | | 3xm=78 | | -3-c/4=12-3c/4 | | .25(12+1)=.5(y+2) | | -170=5(-7-3x) | | -41+20=-7x+14x | | 2x+2.5=-.5(x-1.5) | | 12z-5=6 | | 30/45=2x/x | | 10x-84=4x-12 | | 4z=2.2+2.6 | | 3x-12/9=x |

Equations solver categories